PERSUASIVE POWER AS REFLECTED BY RHETORICAL STYLES IN POLITICAL SPEECHES: A COMPARATIVE STUDY OF BARRACK OBAMA AND JOHN MCCAIN - Rahayu, Famala Eka Sanhadi; Susilo, Susilo; Sunardi, Sunardi (CaLLs (Journal of Culture, Arts, Literature, and Linguistics), 2018)
This study investigated about persuasive power and rhetorical style in Barrack Obama’s and John McCain’s speeches to answer two problems: how Barrack Obama’s and John McCain’s political speeches conveyed persuasive power as reflected in their rhetorical styles and what the differences of Barrack Obama’s political speeches from John McCain’s speeches are in terms of: persuasive power of the message conveyed and the rhetorical style from eighteen speeches during Presidential Election Campaign of United States in 2008. The researcher used rhetorical criticism as the technique in analyzing the data. The data of the present study were sentences which were considered to have persuasive power that were created by using rhetorical style. Having analyzed the data, the researcher revealed the following findings: (1) The researcher found that both Obama and John McCain used rhetorical style to convey the meaning in their speeches. Yet, they produced the rhetorical style differently in case of the time they brought into the speeches; Obama brought the future but McCain brought the past; (2) Obama had more persuasive power in his speech comparing with John McCain since he produced more frequent and more various rhetorical style.